Differences in Reading by the Economic Status of Texas Grade 4 Boys and Girls in Special Education: A Multiyear Statewide Investigation - Pariseau, Matthew M.; Slate, John R; Lunenburg, Frederick C. (International Journal of Social Learning (IJSL), 2021)
In this investigation, the degree to which the economic status (i.e., Not Economically Disadvantaged, Economically Disadvantaged) of Texas Grade 4 boys and girls in special education was related to their reading performance was addressed. Archival data from the Texas Education Agency Public Education Information Management System were analyzed for 2014-2015, 2015-2016, 2016-2017, and 2017-2018 school years on the Texas state-mandated reading assessment for Grade 4 students. Inferential statistical analyses, conducted separately for boys and girls in special education, revealed that boys and girls in poverty had statistically significantly lower reading test scores than boys and girls who were not in poverty. Results in all four school years were consistent with the existing research literature in that poverty negatively affects reading performance. Implications for policy and practice were provided, as well as recommendations for future research.